2005
DOI: 10.1007/s00774-005-0601-z
|View full text |Cite
|
Sign up to set email alerts
|

How many days per week should rats undergo running exercise to increase BMD?

Abstract: The aim of the present study was to examine the effect of different frequencies of running exercise on increasing bone mineral density (BMD) and improving bone histomorphology at various sites of the skeleton (tibia, femur, and second lumbar vertebra) in young rats. Twenty-five female Wistar rats, 8 weeks old, were divided into five groups, of 5 animals each according to running load: control group, no running (A group); running load (RL), 4 days per week (d/w; B group); RL, 5 d/w (C group); RL, 6 d/w (D group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
2
26
2
1
Order By: Relevance
“…The running load was initiated when the rats were 8 weeks old. The running conditions were determined according to our previous publications (Hagihara et al 2000(Hagihara et al , 2005. All rats ran at a treadmill speed of 15 m/min, a speed at which they ran voluntarily and did not drop out.…”
Section: Running Exercise and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The running load was initiated when the rats were 8 weeks old. The running conditions were determined according to our previous publications (Hagihara et al 2000(Hagihara et al , 2005. All rats ran at a treadmill speed of 15 m/min, a speed at which they ran voluntarily and did not drop out.…”
Section: Running Exercise and Proceduresmentioning
confidence: 99%
“…Using young growing rats, we previously verified the effects of moderate exercise in the form of running on a treadmill at a speed of 15 m/min for 30 min per day, over an 8-week period, on BMD of the long bones. We determined that the appropriate exercise frequency to increase BMD of the long bones was 4 to 5 days per week (Hagihara et al 2005). However, the optimal combination of exercise frequency and duration to maximize BMD has not been established.…”
mentioning
confidence: 99%
“…27,28 The lack of consistent opinion is caused by different exercise protocols and participants' cooperation and therefore needs further investigation.…”
Section: Frequency and Type Of Exercises Recommended In Postmenopaumentioning
confidence: 99%
“…The effect of treadmill exercise on bone mass in rodents has been previously studied [8][9][10][11][12]. The time and the degree of the endurance treadmill running training were not uniform in the different studies, although most of them revealed that this type of exercise has effects on bone density, size and shape, resulting in substantial improvements in mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Increased Young's modulus and higher concentration of Ca in femurs of trained rats were also described [9]. In general, increases in bone mineral density (BMD) can be obtained by a moderate running load (15 m/min for 30 min) at frequencies of 4 and 5 days per week [11]. It has also been reported that the effect of exercise on bone at an older age is different from that at other ages [14].…”
Section: Introductionmentioning
confidence: 99%